Improving Literacy Through Read Aloud Picture Books at Klis Christian Elementary School - Fransheine Rumtutuly; Dovila Johanzs (CV. TOTUS TUUS, 2025)
This Community Service Activity aims to improve the literacy of elementary school students through the read-aloud method using picture books at SD Kristen Klis, Klis Village, Pulau Moa District, Southwest Maluku Regency. The background of this activity is the low interest and reading ability of students, caused by the lack of variation in teaching methods and limited vocabulary. The activity was conducted in December 2024 and included several stages: planning, program development, implementation of read-aloud sessions, and evaluation. The picture books used were selected based on the age appropriateness for the students and the inclusion of character values. The read-aloud sessions are conducted expressively and interactively, accompanied by follow-up activities such as drawing, writing short sentences, and discussions. The results of the evaluation through observation and comprehension tests show an increase in reading interest, listening skills, speaking confidence, as well as understanding of the story content and character values. More than 80% of the students were able to correctly answer most of the comprehension questions. In conclusion, the read-aloud method with picture books is effective in enhancing early literacy skills and shaping students' character through enjoyable and meaningful learning experiences.